METODE DAKWAH PADA KALANGAN LANJUT USIA DI MASJID AL-FURQON HAURGEULIS - Khofifi, Moh; Sobirin, Sobirin (Universitas Ahmad Dahlan, 2019)
Elderly people are every Indonesian citizen, male and female, who have reached the age of 60 years and over, whether they have the potentially or not (The decree of the Minister of Social affair of RI No.15/HUK/2007). The objectives of this study are to determine the use of da?wah method for elderly and find out the supporting and inhibiting factors in conducting da?wah to the elderly people at Al-Furqon Mosque. This study applies a qualitative method (field research) for data collection, this study employs structured interview, observation and documentation techniques. The findings of the study show that there is no specific recitation for elderly people at Al-Furqon Mosque almost middle age. Routine recitation is held once a week on Sunday night and Wednesday night. It implements lecturing, holding question and answer and applicative methods. And the second finding, supporting factors of conducting da?wah to elderly people it shows adequate facilities and infrastructure, the right time table this activity, is after Maghrib mass prayer, the use of local languages as means of communication to the send the da?wah message from the preacher, The tolerance of other groups or organizations that are contrary to the culture of the Al-Furqon Mosque, lastly the family support of the elderly people who always motivaty them to be ?Istiqomah? in joining the recitation at family and the inhibiting factor in delivering the message of da?wah to elderly worshipers in terms of psychological and physical perspectives. Are from the psychological lonely, mourning the loss of a loved one and feel depression due to pressure from family. Are from a physical perspective, they experience decreased hearing ability, decreased vision, and immune system that is getting weaker so they are susceptible to disease. So rarely can take part in recitation.